Studies on Cyanex-272 Complexes of Mg (II), Ca (II) and Fe (III) (Bangladesh Journal of Scientific and Industrial Research, 2008)
Certain complex compounds were synthesized by the interaction of Mg(II), Ca(II) and Fe(III) halides with the solvent extracting reagent, Cyanex-272 i.e. bis (2,4,4- trimethylpentyl) phosphinic acid as ligand. All the prepared complexes have been characterized on the basis of their molar masses, conductivity, magnetic measurements and infrared and electronic spectral studies. The other physico-chemical properties e.g. colour, decomposition temperature have also been ascertained. Key words: Chanex-272Bangladesh J. Sci. Ind. Res. 42(4), 475-482, 2007